The Construct Of Muslim Society In The Perspective Of Sayyid Qutb - Greg Soetomo (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2020)
This article aims to explicate the construction of Muslims society in the perspective of Sayyid Qutb. In Qutb’s perspective, the Islamic community has to be built on the same faith, not the other way round. However, as practised by liberal countries today, they found their social hierarchy on race, class, and nationality. It is what he termed as an ideal society that it simultaneously evaluated the life of jahiliyyah (the age of ignorance). Through the exploration of his two masterpieces (The Milestones) Ma'alim fī al-Ṭarīq and Fī Ẓilal al Qur’ān, this research will explicate the construct of Islamic society, which is wished in Qutb’s perspective encompasses several elements including the systems of social, economy, politic, the relationship of individual and society, equality of humans and freedom, attitudes towards the West, and justice’s concept.